Attenuation of skeletal muscle atrophy via acupuncture, electro-acupuncture, and electrical stimulation - T. Brock Symons; Jinho Park; Joo Hyun Kim; Eun Hye Kwon; Jesse Delacruz; Junghoon Lee; Yoonjung Park; Eunhee Chung; Sukho Lee (Integrative Medicine Research)
Background: Accelerated skeletal muscle wasting is a shared trait among many pathologies and aging. Acupuncture has been used as a therapeutic intervention to control pain; however, little is known about its effects on skeletal muscle atrophy and function. The study's purpose was to compare the effects of acupuncture, electro-acupuncture, and electrical stimulation on cast-induced skeletal muscle atrophy. Methods: Forty female Sprague Dawley rats were randomly divided into groups: Control, casted (CAST), CAST+Acupuncture (CAST-A), 4) CAST+Electro-acupuncture (CAST-EA), and CAST+Electrical stimulation (CAST-ES) (n = 8). Plaster casting material was wrapped around the left hind limb. Acupuncture and electro-acupuncture (10 Hz, 6.4 mA) treatments were applied by needling acupoints (stomach-36 and gallbladder-34). Electrical stimulation (10 Hz, 6.4 mA) was conducted by needling the lateral and medial gastrocnemius muscles. Treatments were conducted for 15 min, three times/week for 14 days. Muscle atrophy F-box (MAFbx), muscle RING finger 1 (MuRF1), and contractile properties were assessed. Results: Fourteen days of cast-immobilization decreased muscle fiber CSA by 56% in the CAST group (p = 0.00); whereas, all treatment groups demonstrated greater muscle fiber CSA than the CAST group (p = 0.00). Cast-immobilization increased MAFbx and MuRF1 protein expression in the CAST group (p<0.01) while the CAST-A, CAST-EA, and CAST-ES groups demonstrated lower levels of MAFbx and MuRF1 protein expression (p<0.02) compared to the CAST group. Following fourteen days of cast-immobilization, peak twitch tension did not differ between the CAST-A and CON groups (p = 0.12). Conclusion: Skeletal muscle atrophy, induced by 14 days of cast-immobilization, was significantly attenuated by acupuncture, electro-acupuncture, or electrical stimulation.